Paper 81: Quadriceps Tendon Autograft Yields Good Outcomes for Revision ACL Reconstruction after Failed Patellar Tendon Autograft. Issue 7 (30th July 2022) - Bailey, Lane; Mullane, Aaron; Kleihege, Jacquelyn; Paine, Russell; Flores, Steven; Lowe, Walter; Marconi, Dante
Objectives: Few studies have examined the viability of the quadriceps tendon autograft as a revision graft option following failed primary bone-patellar tendon-bone (PT) autograft reconstruction. Potential concerns include further disruption to the knee extensor mechanism, inhibition of the quadriceps muscle, and increased complication and reinjury rates. The purpose of this study was to assess knee extension strength, functional outcomes, patient reported outcomes, and return to play after revision ACL reconstruction using free quadriceps tendon autograft after a failed primary reconstruction using bone-patellar tendon-bone (PT) autograft. Methods: A retrospective case series was conducted in accordance with Strengthening the Reporting of OBservational Studies in Epidemiology (STROBE) guidelines using a prospective single surgeon ACL database (n = 1, 514) that included 48 patients receiving revision ACL reconstruction using free QT autograft after failure of primary PT autograft ACL reconstruction from 2015-2019. Exclusion criteria are listed in Figure 1, and included ages <15 years or > 55 years, bi-cruciate ligament injuries, and meniscal allograft transplant. Baseline patient demographics and surgical variables were collected and included preinjury level of function (Marx Score). Functional and self-reported outcomes were obtained at the time of return to play and consisted of: single-leg squat symmetry, hip abduction strength, single-leg hop tests, agility testing, and isokinetic knee extension strength (60°, 180°, and 300°/sec). Self-reported outcomes at the time of return to play included the International Knee Disability Committee (IKDC-2000) scale and Anterior Cruciate Ligament–Return to Sport after Injury (ACL-RSI) psychological readiness survey. Return to play was defined as the time (mo) required to reach a threshold of 90% limb symmetry on objective functional testing compared to the contralateral extremity and ultimately, the surgeon's discretion. Injury and complication surveillance was conducted for 2-years postoperatively, and patients were contacted via email or phone survey at 24-months to obtain functional status and single answer numeric evaluation (SANE) scores. Descriptive statistics were calculated using SPSS (version 26, IBM Inc, NY, USA). Results: Baseline patient demographics are listed in Table 1 for the 48 patients (mean age 23.9 ±9.5 years; 14/34 female/male) enrolled in the study. Isokinetic knee extension strength was 84.3 ±17.1% at 60°/sec, 88.6 ±16.4% at 180°/sec, and 92.0 ±19.5% at 300°/sec. The mean knee function SANE score at 2-years was 88.9 ±12.2%. All patients went through return to play testing prior to returning to sport. The mean time to return to play was 8.9 ±1.8 mo, and the mean 24-month assessment was conducted at 24.6 ±2.3 mo. Limb symmetry index scores ranged from 94.1%-102.6% across all objective functional tests (Table 2), and self-reported knee function via the IKDC-2000 was 86.3±16.8. Three patients were lost to follow up (6.3%) at 2-years, and of the 45 patients remaining in the study, 3 sustained graft reinjuries (6.7%). Two-year complications are listed in Table 3, and included meniscal tear (2.2%), DVT (4.4%), loss of motion requiring surgical lysis of adhesions (4.4%), anterior knee pain (11.1%), and symptomatic removal of hardware (2.2%). Conclusions: Free quadriceps tendon autograft is a viable autograft option for revision ACL reconstruction for failed PT autograft allowing return to high function without compromising knee extension strength with a low failure and complication rate. Two-year graft reinjury rates for revision ACL reconstruction with free QT autograft are similar or favorable to other autograft options previously reported in the literature in a revision setting. Additionally, functional outcomes are comparable to revision reconstructions using PT autograft and good to excellent outcomes can be obtained Table 1. Patient Demographics Fig 1. Study Design Table 2. Level of Return to Sport Table 3. Return to Play Functional Performance Outcomes